2011
DOI: 10.1007/s00271-011-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Midday measurements of leaf water potential and stomatal conductance are highly correlated with daily water use of Thompson Seedless grapevines

Abstract: A study was conducted to determine the relationship between midday measurements of vine water status and daily water use of grapevines measured with a weighing lysimeter. Water applications to the vines were terminated on August 24th for 9 days and again on September 14th for 22 days. Daily water use of the vines in the lysimeter (ET LYS ) was approximately 40 L vine -1 (5.3 mm) prior to turning the pump off, and it decreased to 22.3 L vine -1 by September 2nd. Pre-dawn leaf water potential (W PD ) and midday … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
25
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 56 publications
(72 reference statements)
9
25
1
1
Order By: Relevance
“…Based on our findings using C Stem as our stress proxy, one might expect that the roots are forming lacuna even under well-watered conditions. However, during the initial stages of soil drying following an irrigation or precipitation event, the C PD will typically be in the range of 20.1 to 20.3 MPa (Williams et al, 2012). As the soil dries, the C PD of the plant begins to drop and will enter the range at which lacuna formation can occur; various studies have documented C PD values of 20.5 to 21.1 MPa in grapevines that depend on the duration of a drought event (intermittency of irrigation), soil type, climate, variety, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings using C Stem as our stress proxy, one might expect that the roots are forming lacuna even under well-watered conditions. However, during the initial stages of soil drying following an irrigation or precipitation event, the C PD will typically be in the range of 20.1 to 20.3 MPa (Williams et al, 2012). As the soil dries, the C PD of the plant begins to drop and will enter the range at which lacuna formation can occur; various studies have documented C PD values of 20.5 to 21.1 MPa in grapevines that depend on the duration of a drought event (intermittency of irrigation), soil type, climate, variety, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Williams and Trout (2005) found that measurement of soil water content to a depth of 3m at nine locations within one-quarter of an individual vine root zone was necessary to accurately determine the amount of water within the soil profile available to drip-irrigated vines. Also, a given soil volumetric water content may induce differing severities of water stress in different grapevine cultivars due to intrinsic differences among cultivars in their hydraulic behavior ranging from isohydric to anisohydric (Schultz, 2003;Shellie and Bowen 2014;Williams et al, 2012;Bellvert et al, 2015a). Thus, bulk changes in soil water content or soil water potential may not correspond with changes in vine water status (Jones, 2004;Williams and Trout, 2005;Ortega-Farias et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Williams and Trout (2005) found that pre-dawn leaf water potential was unsatisfactory for accurately determining vine water status while midday leaf and stem water potential were linearly correlated and equally suitable for determining vine water status. Midday leaf water potential is the most common method used in California to indicate vine water status (Williams et al, 2012) perhaps because it is less time consuming than either predawn leaf water potential or midday stem water potential allowing more acreage to be covered during midday climatic conditions (Williams and Araujo, 2002). Midday stem and leaf water potential of grape vines are highly correlated with vapor pressure deficit (VPD) under semi-arid conditions but the correlations differ for leaf water potentials less than or greater than 1.2 MPa (Williams and Baeza, 2007;Williams et al, 2012) In general, a midday value of leaf water potential less negative than −1.0 MPa under high evaporative demand has generally been accepted as indicative of well-watered vines (Shellie, 2006;Williams and Trout, 2005;Williams et al, 2012;Shellie and Bowen, 2014;Bellvert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(McCutchan and Shackel, 1992) or grapevines (Williams and Baeza, 2007) and they can be a useful tool for irrigation scheduling based on the plant water status. The water potential has been used as a scheduling irrigation tool for deciduous fruit trees (Shackel et al, 1997), grapevines (Girona et al, 2006;Williams et al, 2012) and olive trees (Moriana et al 2012). The water deficit in the C treatment was prevented with irrigation water amounts lower than those calculated using just the Penman-Monteith equation.…”
Section: Soil Water Content and Evapotranspiration Measurementsmentioning
confidence: 99%
“…The water potential has been used as a scheduling irrigation tool for deciduous fruit trees (Shackel et al, 1997), grapevines (Girona et al, 2006;Williams et al, 2012) and olive trees (Moriana et al 2012). Goldahmer, 1995).…”
Section: Plant Water Relationsmentioning
confidence: 99%